APPLICATION OF BEHAVIORAL COUNSELING MODELING TECHNIQUES TO IMPROVE THE SELF-CONFIDENCE OF STUDENTS WITH INTELLECTUAL DISABILITIES IN SOPPENG - Sri Kumalasari; Abdul Saman; Usman Bafadal (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effectiveness of applying behavioral counseling with modeling techniques to improve the self-confidence of eleventh-grade students with intellectual disabilities at SLB As’Adiyah Cabenge, Soppeng Regency. This research employed a quantitative approach with an A-B-A-B Single Subject Research (SSR) experimental design. Data collection techniques involved observation sheets in the form of a checklist assessment scale during the experiment (Baseline B1-B2) intervention when applying behavioral counseling techniques with modeling techniques. Data were analyzed using descriptive statistics, both within and between conditions. The results showed that the application of behavioral counseling with modeling techniques had a significant impact on increasing the self-confidence of students with intellectual disabilities. This was evident from the increase in scores during the intervention phase (B1) compared to the initial baseline phase (A1), as well as the stability of scores in the final baseline phase (A2), indicating that the intervention effect was sustainable. Repeated intervention in phase (B2) also showed higher score increases compared to baseline phase 2 (A2). There were clear changes between baseline A1, intervention B1, baseline A2, and intervention B2. At baseline A1, students showed low self-confidence (average score 50), but then increased to 55.7–72 in the B1 intervention phase. The sustainability of the intervention effect was observed in the baseline A2 phase, where the obtained score of 55.7 increased to 61.5. Subsequently, the intervention (B2) was repeated, resulting in a score increase from 61.5 to 75. Thus, this intervention was effective in increasing the self-confidence of students with intellectual disabilities at SLB As’Adiyah Cabenge, Soppeng Regency.